The Gecko and Sticky : the power potion - Van Draanen, Wendelin (Van Draanen, Wendelin. Gecko & Sticky, 2010)
Thirteen-year-old Dave and Sticky, his kleptomaniac sidekick gecko, try to keep a special potion from falling into the hands of the diabolical Damien Black.